Stepwise Climate-Smart Cocoa pilots in the cope and adjust climate impact zones - Dalaa, Mustapha Alasan; Kofituo, Rich Kofi; Asare, Richard (International Institute of Tropical Agriculture, 2020)
As part of efforts in developing a business case for investing in climate-smart cocoa (CSC) practices, IITA has partnered with Public and Private sector organizations (PBC and CARGILL respectively) in the cocoa industry to co-learn on tailored made climate-smart cocoa practices in Ghana. A collaboration agreement has been signed between IITA and the companies to run CSC pilots for a period of 12 months. The end goal is to introduce farmers to the CSC practices through a co-learning process and to co-generate CBA data on each CSC practice through the establishment of stepwise CSC Pilots in two cocoa climate impact zones. This is expected to enhance the adoption and scaling-up of climate-smart cocoa by the companies and other stakeholders in the cocoa industry.